Outcomes and Risk Factors of Septic Shock in Patients With Infective Endocarditis: A Prospective Cohort Study. (25th March 2021) - Pericàs, Juan M; Hernández-Meneses, Marta; Muñoz, Patricia; Álvarez-Uría, Ana; Pinilla-Llorente, Blanca; de Alarcón, Arístides; Reviejo, Karlos; Fariñas, M Carmen; Falces, Carlos; Goikoetxea-Agirre, Josune; Gálvez-Acebal, Juan; Hidalgo-Tenorio, Carmen; et al.
Abstract: Background: Little is known about the characteristics and impact of septic shock (SS) on the outcomes of infective endocarditis (IE). We aimed to investigate the characteristics and outcomes of patients with IE presenting with SS and to compare them to those of IE patients with sepsis (Se) and those with neither Se nor SS (no-Se-SS). Methods: This is a prospective cohort study of 4864 IE patients from 35 Spanish centers (2008 to 2018). Logistic regression analyses were performed to identify risk factors for SS and mortality. Results: Septic shock and Se presented in 597 (12.3%) and 559 (11.5%) patients, respectively. Patients with SS were younger and presented significantly higher rates of diabetes, chronic renal and liver disease, transplantation, nosocomial acquisition, Staphylococcus aureus, IE complications, and in-hospital mortality (62.5%, 37.7% for Se and 18.2% for no-Se-SS, P < .001). Staphylococcus aureus (odds ratio [OR], 1.94; 95% confidence interval [CI], 1.34–2.81; P < .001), Gram negative (OR, 2.21; 95% CI, 1.25–3.91; P = .006), nosocomial acquisition (OR, 1.44; 95% CI, 1.07–1.94; P = .015), persistent bacteremia (OR, 1.82; 95% CI, 1.24–2.68; P = .002), acute renal failure (OR, 3.02; 95% CI, 2.28–4.01; P < .001), central nervous system emboli (OR, 1.48; 95% CI, 1.08–2.01; P = .013), and larger vegetation size (OR, 1.01; 95% CI, 1.00–1.02; P . = 020) were associated with a higher risk of developing SS. Charlson score, heart failure, persistent bacteremia, acute renal failure, mechanical ventilation, worsening of liver disease, S aureus, and receiving aminoglycosides within the first 24 hours were associated with higher in-hospital mortality, whereas male sex, native valve IE, and cardiac surgery were associated with lower mortality. Conclusions: Septic shock is frequent and entails dismal prognosis. Early identification of patients at risk of developing SS and early assessment for cardiac surgery appear as key factors to improve outcomes. Abstract : Septic shock and sepsis presented in 12.3% and 11.5% patients, respectively, with endocarditis. Septic shock is associated to very high mortality rates. Cardiac surgery is associated to lower mortality in patients with septic shock.